Optimal flexible solutions of capacity benefit margin considering interconnected system reliability - Muhammad Murtadha, Othman; Nurulazmi, Abd Rahman; Daw salleh, Sasi; Ismail, Musirin, Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org/